Handbook of Maleic Anhydride Based Materials Syntheses, Properties and Applications - Musa, Osama M. (Springer International Publishing : Imprint: Springer, 2016)
A handbook on syntheses and properties, production processes, and applications of maleic anhydride and maleic anhydride derived products - all in one text. This handbook provides a comprehensive overview of maleic anhydride chemistry and applications from the professional perspective. With chapters written by leading R&D scientists from the chemical industry, and edited by the Vice President and ASI Technology Chief at Ashland Specialty Ingredients (ASI), Dr. Osama M. Musa, readers will find a unique perspective and summary of the latest advancements in the field of maleic anhydride science. Maleic anhydride is produced industrially on large scale (10E3 kt/annum). Its rich chemistry makes it an important raw material for numerous products and processes (e.g. for applications in polymers and coatings), many of which are covered in this handbook for the first time in a comprehensive manner. The broad scope spans topics ranging from production techniques (including topics such as processes, catalysis, trouble-shooting), synthesis and properties of small and polymeric maleic anhydride based compounds (focusing on industrially relevant compounds as well as emerging areas of importance) and in-depth and broad discussions of commercial maleic anhydride based applications.